Formation of cultural images of Slovenia in Czech journalism of the nineteenth century and their traces in contemporary memory - Kozár, Aleš (My University, 2024)
During the nineteenth century, in the Czech press we can see the formation of symbolic images of Slovenes and Slovene culture and its history and culture that accompanied the development of mutual awareness of both countries and cultures. The intensity of these ties culminated at the beginning of the twentieth century in all areas of the contact between the two countries. During the twentieth century, thanks to both world wars and the political changes they caused, as well as due to the estrangement of both regimes during the 1950s, these relations underwent partial degradation, accompanied by erosion of awareness of Slovenian culture in what was then Czechoslovakia. The period after 1991 is accompanied by active reminders of entirely or partially vanished symbols and narratives of mutual relations (Plečnik, Majar Ziljski, Lego, Gallus, Kvederová, etc.) through events (exhibitions, conferences) or by building places of memory (memorial plaques, repair of gravestones, etc.). The study attempts to point out the evolution of some of these symbolic images and their forgetting/remembrance today.
Utváření kulturních obrazů Slovinska v české publicistice 19. století a jejich stopy v paměti dneška
Keywords: cultural images; Slovenian culture; cultural stereotypes; Czech media; Czech-Slovenian relations; kulturní obrazy; slovinská kultura; kulturní sterotypy; česká média; česko-slovinské vztahy